2009
DOI: 10.1002/job.629
|View full text |Cite
|
Sign up to set email alerts
|

Perceived support in a dual organizational environment: Union participation in a university setting

Abstract: SummaryThere is extensive research on employee attitudes regarding employers and unions, but these studies have underemphasized social and affective forces. Most studies also examine attitudes toward either the union or the employer without considering how these attitudes might relate to one another. The present study of faculty (N ¼ 306) at a large public research university demonstrated that perceptions of union support were positively related to union participation and perceptions of administration support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 73 publications
1
25
2
1
Order By: Relevance
“…Os colaboradores que experienciam o empenhamento organizacional afetivo tendem a valorizar sua associação com a organização, encontrando-se mais motivados para contribuir positivamente com o desempenho organizacional (Goeddeke & Kammeyer-Mueller, 2010;Kuvaas, 2006;Meyer & Herscovitch, 2001;Meyer & Smith, 2000), porque o resultado é bastante positivo.…”
Section: Discussionunclassified
“…Os colaboradores que experienciam o empenhamento organizacional afetivo tendem a valorizar sua associação com a organização, encontrando-se mais motivados para contribuir positivamente com o desempenho organizacional (Goeddeke & Kammeyer-Mueller, 2010;Kuvaas, 2006;Meyer & Herscovitch, 2001;Meyer & Smith, 2000), porque o resultado é bastante positivo.…”
Section: Discussionunclassified
“…If members sense that their employer is hostile to the union, they may be less committed to the union (Fuller and Hester 1998) and are probably going to be less active in it for fear that such activism may be seen as disloyal or an indication that the employee is "not serious" about his or her career advancement. Goeddeke and Kammeyer-Mueller (2010) found that perception of a hostile employer attitude toward the union reduced union participation.…”
Section: Limitationsmentioning
confidence: 97%
“…The union has nothing to offer them. Recent research indicates that if the union cannot deliver on its tangible benefits, employees will not want to participate in a union, despite the potential for support and social exchange (Goeddeke & Kammeyer-Mueller, 2009). This is the category into which formerly pro-union, strong exchange ideology employees would be placed (see Fig.…”
Section: Rtw and Decertification: Dissolution Of Bond And The Unionmentioning
confidence: 98%